SUSCEPTIBILITY OF SOME COWPEA VARIETIES TO THE SEED BEETLE, CALLOSOBRUCHUS MACULATUS (F.)(COLEOPTERA: CHRYSOMELIDAE) - Musa, Abdulrassak Kannike (Journal of Agricultural Sciences (Belgrade), 2017)
ABSTRACT The study evaluated seven cowpea Vigna unguiculata L. Walp. varieties: IT89K-568-18, IFE-98-12, IT81P-994, IT89K-288, IT96-660, `Milk` and `Drum` for susceptibility to the seed beetle, Callosobruchus maculatus (F.) (Coleoptera: Chrysomelidae). Seed samples (100 g) of each variety were infested with 5 pairs of the seed beetle (1-2 days old) with three replications at 30±20C and relative humidity of 69-72%. The parameters evaluated include: number of damaged and undamaged seeds, percentage seed weight loss, mean number of emerged adults, median development period and susceptibility index. The percentage seed weight loss in IT96-660 was significantly (p<0.05) higher than IT89K-568-18, IT89K-288 and `Milk`. The mean number of seeds damaged in IFE-98-12 was significantly (p<0.05) higher than IT89K-568-18, IT81P-994, IT89K-288, IT96-660 and `Milk`. The median developmental period in `Milk` was significantly (p<0.05) higher than IT89K-568-18, IFE-98-12, IT96-660 and `Drum`. IFE-98-12 and IT89K-568-18 with susceptibility index of 10.4 and 7.8 were rated highly susceptible and moderately susceptible, respectively. Number of emerged adults was highly significant and positively correlated with percentage seed weight loss. Results obtained showed that these cowpea varieties were relatively susceptible to C. maculatus attack in storage suggesting the need for their proper preservation against the insect.